2014
DOI: 10.1039/c3mb70314b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on beta and delta isoform-specific binding mechanisms of phosphoinositide 3-kinase inhibitors

Abstract: Phosphoinositide 3-kinase (PI3K) is known to be closely related to tumorigenesis and cell proliferation, and controls a variety of cellular processes, including proliferation, growth, apoptosis, migration, metabolism, etc. The PI3K family comprises eight catalytic isoforms, which are subdivided into three classes. Recently, the discovery of inhibitors that block a single isoform of PI3K has continued to attract special attention because they may have higher selectivity for certain tumors and less toxicity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…According to the previous studies, MM/GBSA usually provides reliable ranking results rather than accurately predicting the absolute binding free energies. [45,54,65] According to the calculation results, COM25 has the strongest inhibition to GSK3β than CDK2 and its predicted binding free energy for GSK3β is the highest. COM23 has lower potency for GSK3β, and its selective activity against CDK2 is lower than COM25.…”
Section: Binding Free Energy Calculationssupporting
confidence: 75%
See 2 more Smart Citations
“…According to the previous studies, MM/GBSA usually provides reliable ranking results rather than accurately predicting the absolute binding free energies. [45,54,65] According to the calculation results, COM25 has the strongest inhibition to GSK3β than CDK2 and its predicted binding free energy for GSK3β is the highest. COM23 has lower potency for GSK3β, and its selective activity against CDK2 is lower than COM25.…”
Section: Binding Free Energy Calculationssupporting
confidence: 75%
“…The calculated binding affinities are much stronger than the experimental data. According to the previous studies, MM/GBSA usually provides reliable ranking results rather than accurately predicting the absolute binding free energies . According to the calculation results, COM25 has the strongest inhibition to GSK3β than CDK2 and its predicted binding free energy for GSK3β is the highest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ΔG GB was calculated by the Generalized Born (GB) model with the parameters developed by Onufriev et al (igb = 2); [43] ΔG GA was estimated based on the solventaccessible surface area (SASA) with a fast linear combination of the pairwise overlap (LCPO) algorithm using a probe radius of 1.4 Å: [44] ΔG SA = 0.0072 × ΔSASA; À TΔS the change of conformation entropy upon ligand binding would not be calculated here because of expensive computational cost and low prediction accuracy. [45][46][47][48][49] In the ΔG GB calculations, the exterior dielectric constant was set to 80, and the solute dielectric constant was set to 1. [50,51] All energy components were calculated using the MM_PBSA program of AMBER16 based on 5000 snapshots evenly extracted from 50 to 100 ns.…”
Section: Binding Free Energy Calculations and Decompositionmentioning
confidence: 99%
“…It has been reported that the combinatory effort of comparative molecular field analysis (CoMFA), comparative molecular similarity induces analysis (CoMSIA), docking analysis and MD simulation can elucidate the structure-activity correlation of the inhibitors of p110α, as well as the binding modes of inhibitors at the ATP binding pocket [152]. Furthermore, the free energy calculations are used to select and confirm the isoform-specific inhibitors to p110α, p110β or p110δ, in silico [153,154]. So far, ten PI3K inhibitors of high isoform specificity are under clinical trials [104].…”
Section: Molecular Dynamics Simulation Inspires a New Generation Omentioning
confidence: 99%